Ski Mountaineering: Perspectives on a Novel Sport to Be Introduced at the 2026 Winter Olympic Games - Bortolan, Lorenzo; Savoldelli, Aldo; Pellegrini, Barbara; Modena, Roberto; Sacchi, Massimiliano; Holmberg, Hans-Christer; Supej, Matej (Frontiers in Physiology, 2021)
In recent years, participation in ski mountaineering and media coverage of this sport have grown dramatically, leading to proposals that it be included in the 2026 Winter Olympics in Milano-Cortina. Here, our aim was to describe the major characteristics of ski mountaineering, as well as to consider its future. The ascent and descent of largely unprepared slopes involved require pronounced physiological capacity and remarkable downhill skiing ability, respectively. The five official World Cup races differ with respect to length, the total vertical gain and the distribution of downhill and uphill sections. The physiological effort required is dependent not only on the type and duration of the race, but is also influenced by the elevated altitude and typically low temperatures, factors that should be considered in connection with both training and testing. The positive correlation between maximal oxygen uptake (VO2max) and second ventilatory threshold (VT2), on the one hand, and race time (especially when normalized to body mass) on the other indicates that pronounced aerobic capacity is an important determinant of success in ski mountaineering. The future development of this sport would benefit from more extensive collaboration between researchers, industrial actors and the athletes, coaches, and organizers themselves. Among other advances, wearable technology designed specifically to analyze ski mountaineering performance and optimize training should be developed. In addition, new formats for competition in combination with technology designed for real-time viewing by both spectators along the tracks and television audiences could enhance the popularity of this sport considerably.